(System Function)
 
(7 intermediate revisions by the same user not shown)
Line 10: Line 10:
 
<math>H(j\omega)=\int_{-\infty}^\infty h(\tau)e^{-j\omega\tau}d\tau</math>
 
<math>H(j\omega)=\int_{-\infty}^\infty h(\tau)e^{-j\omega\tau}d\tau</math>
  
In this case, we can apply the sifting property to arrive at the system function quite easily.  After applying the property, we arrive at <math>H(j\omega)=2-e^{-2j\omega}</math>.  One might recognize this is the Laplace transform of the impulse response.
+
In this case, we can apply the sifting property to arrive at the system function quite easily.  After applying the property, we arrive at <math>H(j\omega)=2-e^{-2j\omega}</math>.  One might recognize this is the Laplace transform of the impulse response evaluated at <math>s=j\omega</math>.
  
 
==Response to a Signal from Question 1==
 
==Response to a Signal from Question 1==
Line 18: Line 18:
  
 
Since we have represented the original signal as a sum of complex exponentials, we simply have to multiply each term of the original input signal by <math>H(j\omega)</math> to obtain the corresponding term in the output.
 
Since we have represented the original signal as a sum of complex exponentials, we simply have to multiply each term of the original input signal by <math>H(j\omega)</math> to obtain the corresponding term in the output.
 +
 +
<math>y(t)=H(jw)x(t)</math>
 +
 +
<math>y(t)=(2-e^{6j})(\frac{1+j}{2}e^{-3jt})-(2-e^{4j})(\frac{7}{2j}e^{-2jt})+(2-e^{-4j})(\frac{7}{2j}e^{2jt})+(2-e^{-6j})(\frac{1+j}{2}e^{3jt})</math>
 +
 +
Which after a little math becomes
 +
 +
<math>y(t)=(1+j)e^{-3jt}-\frac{1+j}{2}e^{-3j(t-2)}-\frac{7}{j}e^{-2jt}+\frac{7}{2j}e^{-2j(t-2)}+\frac{7}{j}e^{2jt}-\frac{7}{2j}e^{2j(t-2)}+(1+j)e^{3jt}-\frac{1+j}{2}e^{3j(t-2)}</math>
 +
 +
It is fairly easy to see that the final <math>y(t)</math> is simply the weighed sum of the doubled input <math>y'(t)=2x(t)</math> and the shifted input <math>y''(t)=x(t-2)</math>.  This can serve as confirmation that the system <b>actually was</b> both linear and time invariant.

Latest revision as of 13:40, 26 September 2008

A Continuous Time, Linear, Time-Invariant System

Consider the system $ y(t)=2x(t)-x(t-2) $.

Unit Impulse Response

Let $ x(t)=\delta(t) $. Then $ h(t)=2\delta(t)-\delta(t-2) $.

System Function

As discussed in class, the system function is

$ H(j\omega)=\int_{-\infty}^\infty h(\tau)e^{-j\omega\tau}d\tau $

In this case, we can apply the sifting property to arrive at the system function quite easily. After applying the property, we arrive at $ H(j\omega)=2-e^{-2j\omega} $. One might recognize this is the Laplace transform of the impulse response evaluated at $ s=j\omega $.

Response to a Signal from Question 1

I will use my signal from Question 1.

$ x(t)=7\sin(2t)+(1+j)\cos(3t)=\frac{1+j}{2}e^{-3jt}-\frac{7}{2j}e^{-2jt}+\frac{7}{2j}e^{2jt}+\frac{1+j}{2}e^{3jt} $

Since we have represented the original signal as a sum of complex exponentials, we simply have to multiply each term of the original input signal by $ H(j\omega) $ to obtain the corresponding term in the output.

$ y(t)=H(jw)x(t) $

$ y(t)=(2-e^{6j})(\frac{1+j}{2}e^{-3jt})-(2-e^{4j})(\frac{7}{2j}e^{-2jt})+(2-e^{-4j})(\frac{7}{2j}e^{2jt})+(2-e^{-6j})(\frac{1+j}{2}e^{3jt}) $

Which after a little math becomes

$ y(t)=(1+j)e^{-3jt}-\frac{1+j}{2}e^{-3j(t-2)}-\frac{7}{j}e^{-2jt}+\frac{7}{2j}e^{-2j(t-2)}+\frac{7}{j}e^{2jt}-\frac{7}{2j}e^{2j(t-2)}+(1+j)e^{3jt}-\frac{1+j}{2}e^{3j(t-2)} $

It is fairly easy to see that the final $ y(t) $ is simply the weighed sum of the doubled input $ y'(t)=2x(t) $ and the shifted input $ y''(t)=x(t-2) $. This can serve as confirmation that the system actually was both linear and time invariant.

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett